Efektivitas Peranan Majelis Pengawas Daerah (MPD) Kota Batam dalam Penegakan Kode Etik Berdasarkan Undang-Undang Nomor 2 Tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris (Studi Lapangan Di Kota Batam) - Johnson Wijaya; Diana Diana (Journal of Judicial Review, 2019)
The implementation of this research was carried out with the aim of knowing the concept of the application of supervisory by the investigator and the effectiveness of the application of the diversion to the Notary who violated the Notary code of ethics in the Batam city area. This research was carried out by the author using empirical legal research methods because in this study the authors used primary data that the author obtained from the Notary investigator, especially in the Batam City Regional Supervisory Assembly unit through interviews and collecting data relating to cases that occurred in the field then the authors review it using the theory of legal effectiveness that was presented by legal expert Soejono Soekanto on the application of diversions that have been carried out within the Batam City area and the authors also review using secondary data in the form of several literature literature and legal science books relating to the subject matter which the author carefully in this thesis. Based on the results of the research that the author has done, it can be concluded that the application of sanctions by the Supervisory party at the investigation stage is still considered to be not fully effective as reviewed based on the theory of legal effectiveness presented by legal expert Soejono Soekanto